Complete chloroplast genome sequence of Populus pruinosa Schrenk from PacBio Sequel II Platform. Issue 3 (2nd July 2020) - Gai, Zhong-Shuai; Liao, Rui; Jiang, Zhen-Bo; Jiao, Pei-Pei; Zhang, Shan-He; Qin, Rui; Liu, Hong; Wu, Zhi-Hua; Li, Zhi-Jun
Abstract: Populus pruinosa Schrenk plays an important role on ecological services in desert areas. The complete chloroplast genome was reported in this study using the PacBio Sequel II Platform. The chloroplast genome with a total size of 157, 856 bp consists of two inverted repeats (IR, 27, 673 bp) separated by a large single-copy region (LSC, 85, 867 bp) and a small single-copy region (SSC, 16, 645 bp). Further annotation revealed the chloroplast genome contains 111 genes, including 78 protein-coding genes, 29 tRNA genes, and 4 rRNA genes. A total of 151 simple sequence repeats (SSRs) were identified in the chloroplast genome. This information will be useful for study on the evolution and genetic diversity of P. pruinosa in the future.